2020
DOI: 10.12982/vis.2021.006
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii and Neospora caninum prevalence and risk factors on goat farms in Kanchanaburi province, Thailand

Abstract: Toxoplasma gondii and Neospora caninum are apicomplexan protozoan parasites that have been associated with reproductive problems in ruminants. Despite the high seroprevalence of T. gondii and N. caninum reported in goats worldwide, little information about the seroprevalence of these parasites in goats in Thailand. In this study, we investigated the seroprevalence of T. gondii and N. caninum in 389 goat samples from five districts of Kanchanaburi province, Thailand. An indirect enzyme-linked immunosorbent assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 11 publications
2
14
2
Order By: Relevance
“…Moreover, for this parasite, animal species and location had significant effects on the seroprevalence, with sheep being more affected than goats and northern and eastern Egypt being more affected than middle and southern Egypt. Other authors have also reported significant effects of location and animal species on N. caninum seroprevalence in small ruminants [ 30 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, for this parasite, animal species and location had significant effects on the seroprevalence, with sheep being more affected than goats and northern and eastern Egypt being more affected than middle and southern Egypt. Other authors have also reported significant effects of location and animal species on N. caninum seroprevalence in small ruminants [ 30 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 98%
“…The seroprevalence of T. gondii in domestic and wild animals in Thailand has been investigated in the past [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. However, there are few reports on T. gondii infection in elephants.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of anti-T. gondii antibodies in Thai people is 3.1-53.7% [5][6][7][8]. T. gondii antibodies have been detected in cats [9][10][11], dogs [9,12], cattle [13][14][15], chickens [16], and goats [17,18]. The seroprevalence in captive wild felids in Thailand was reported as 15.4-42.8% [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, they have been considered as a good serodiagnostic test for the detection of T. gondii antibodies both in animals and humans [21]. Many recombinant antigens have been previously studied, namely, GRA1 [21][22][23][24], GRA2 [25][26][27], GRA4 [11], GRA5 [19,28], GRA6 [26,29], GRA7 [18,[21][22][23][24]26,[30][31][32][33], GRA8 [34,35], and GRA15 [26]. GRA7 provides a very strong humoral immune response in the acute stage of infection [3] and is also recognized as a good serological marker for anti-T. gondii detection in the chronic stage [23,31].…”
Section: Introductionmentioning
confidence: 99%
“…GRA7 provides a very strong humoral immune response in the acute stage of infection [3] and is also recognized as a good serological marker for anti-T. gondii detection in the chronic stage [23,31]. Recombinant protein GRA7 has been constructed and evaluated for improving the diagnosis of T. gondii infection worldwide, in humans [18,36], dogs [23], cattle [30], pigs [37], chickens [21], and goats [33]; however, there has been a few reports for cats [26,31,32]. Most recombinant GRA7 proteins for T. gondii diagnosis are commonly performed using an Escherichia coli expression system.…”
Section: Introductionmentioning
confidence: 99%